Biochemical and pathogenic variation in strains of Xanthomonas campestris pv. mangiferaeindicae from Southern India - S.S. GNANAMANICKAM, B.V. DAYAKAR and (Indian Phytopathology, 2002)
Variations in 20 isolates of X. c. pv. mangiferaeindicae (the causal agent of bacterial leaf spot or canker of mango) collected from mango growing areas of Andhra Pradesh, Kerala, Karnataka and Tamil Nadu, were analysed. These isolates varied in their ability to liquefy gelatin, reduce nitrate and utilize carbon sources. In sensitivity to antibiotics, they showed resistance to kanamycin (50 mug/ml) and were sensitive to rifampicin (150 mug/ml). In further analysis, 20 isolates gave 10 distant disease reaction patterns suggesting the presence of 10 pathotypes or races among the 20 strains examined. Among the 6 varieties, Alphanso was highly susceptible and Bangalora was resistant towards most of the isolates. Each of the pathotype groups was represented by 1, 2 or >2 strains which suggested that the pathogen is highly heterogeneous in a particular location.